Kontrasepsi hormonal, riwayat preeklampsia dan hipertensi kronik berhubungan dengan kejadian preeklampsia - Wanda Riskyna Harmawan (Jurnal Medika : Karya Ilmiah Kesehatan, 2022)
Preeclampsia-eclampsia is the cause of almost 75% of deaths in pregnant women worldwide. In Indonesia, hypertension in pregnancy is the most dominant cause. Preeclampsia is hypertension in pregnancy with proteinuria or without proteinuria with disorders of one or more organs. The researcher conducted this study to determine the relationship between a history of hormonal contraception, a history of preeclampsia and chronic hypertension with cases of preeclampsia at Abdul Wahab Sjahranie Hospital, Samarinda. Case control design. The sample was taken from the medical record data of 48 cases and 48 controls who gave birth at the Abdul Wahab Sjahranie Hospital, Samarinda for the period January 2020 - September 2021. The bivariate analysis used by the researcher was the Chi-Square test. The results of the Chi-Square test on a history of using hormonal contraception (p=0.025), chronic hypertension (p=0.001), a history of preeclampsia (p=0.004). It was concluded that there was a relationship between a history of hormonal contraceptive use, a history of preeclampsia, and chronic hypertension with the incidence of preeclampsia.